Implementation Of Hospital Management Information System (SIMRS) At Royal Prima Hospital - Desy Lailani Ferdianti; Sri Lestari Ramadhani Nasution; Ermi Girsang; Tan Suryono (CV. Inara, 2022)
The health information system is part of the national health system (SKN), therefore the health system in Indonesia and health information are needed by hospitals. This concept is needed for the development of a hospital management information system (SIMRS), a puskesmas information system (SIP) and a clinicalinformation system (Handayani, 2020). The purpose of this study was to determine the analysis of theapplication of hospital management information systems (SIMRS) at RSU Royal Prima. The method in this research is qualitative. The population in this study amounted to 10 respondents. The results of the study show that SIMR is very influential on patient care, HR can use the SIMRS application and there is management support in theuse of SIMRS at Royal Prima Hospital Medan. Based on the results of research on the analysis of the application of hospital management information systems (SIMRS) at Royal Prima Hospital, it can be concluded that the quality of the system is still not good in the quality of the system in the field because the internet network problem is not good, the quality of system information has been very helpful for service, the quality of service is very good. , HR is different, new employees are the same as the old ones, if new employees haven't, so new employees should want to learn with old employees, and old employees are proficient in using SIMRS, management supports it because this is indeed a program from management, SIMRS Royal Prima Medan is there The advantages are in patient care and the quality of information systems, all service data at RSU Royal Prima Medan can be stored properly and nicely. It is hoped that the hospital will pay more attention to and improve the quality of the SIMRS internet network at RSU Royal Prima and provide training to all employees, especially for new employees on how to use SIMRS so that services at RSU Royal Prima Medan runsmoothly and well.